ANALISIS TELUR CACING SOIL TRANSMITTED HELMINTH (STH) PADA MURID SDN 5 DWITUNGGAL RANGSANG KAB KEPULAUAN MERANTI - Berliana N.R.S. Aritonang (Jurnal Sains dan Teknologi Laboratorium Medik, 2021)
Ministry of Health Indonesia in 2006, helminthiasis is one of the endemic problems that can be found in various places in Indonesia. Worms are problem that mostly affects elementary school children due to personal hygiene and poor environmental sanitation. The purpose of this study was to determine the presence or absence of Soil Transmitted Helminth (STH) worm eggs in students of SDN 5 Dwitunggal Rangsang in Kepulauan Meranti. The research applied direct and sedimentation methods. Based on microscopic examination with sedimentation method, the results of the research indicated one positive sample of Trichuris trichiura out 27 samples studied.